Toe walking after three: how serious could it be?. (30th May 2018) - Ustaris, Linda-Marie; Seidman, Roberta; Bindra, Tejwant; Basak, Ratna
Abstract : A 4-year-old girl with no significant medical or family history presented with toe walking, leg pain, unsteady gait and frequent falls for 2 months. Examination revealed upper motor neuron signs in the lower extremities. Laboratory tests were normal including creatinephosphokinase and lactate dehydrogenase. Brain and lumbar spine MRI were normal. MRI cervical and thoracic spine showed a large intradural and extradural mass arising from the right C7 nerve root, widening of the neural canal with evidence of cord compression. She underwent C6–C7 laminectomy with excision of the tumour. Pathology revealed spindle cell tumour with extensive expression of S100 protein and CD56, with Ki-67 proliferation index of 1%–2% consistent with benign schwannoma. She made an excellent recovery following surgery and physiotherapy sessions. Review of literature shows rare reported case of schwannoma prior to the third decade of life.